Financial Development and Economic Growth Impact on the Environmental Degradation in Jordan - Jreisat, Ammar (International Journal of Energy Economics and Policy, 2021)
Conflicting results exist in the literature on the role of financial development and economic growth on environmental degradation. The study's focus is to investigate the influence of economic growth and financial development on environmental degradation. The study examines the impact of financial development and economic growth on environmental degradation in Jordan. The ordinary least square model results depict the significant positive impact of financial development on environmental degradation in fossil energy consumption, urbanization, and trade openness as a control variable. Results base the data from 1976 to 2018 for the economy of Jordan. Some control variables also have an insignificant positive impact on carbon emission, a proxy of environmental degradation. This study recommends Jordan's policymakers push the banking and non-banking financial institutions to provide loaning to facilitate the green and environmentally friendly projects, which causes decreased carbon dioxide emissions. Keywords: Energy; Environment; Degradation; Urbanization; Trade. JEL Classifications: Q43, Q50, O44, O16, F62 DOI: https://doi.org/10.32479/ijeep.11161